William Byrd and His Contemporaries : Essays and a Monograph - Brett, Philip (Book collections on Project MUSE., 2007)
Throughout his career, Philip Brett wrote about the music of the Tudor period. He carried out pathbreaking work on the life and music of William Byrd (c1540-1628). Collecting these influential essays, this volume is a tribute to Brett's agile mind and to his incomparable skill at synthesising history and musical analysis.